Professional Practice for Architects and Project Managers - Chappell, David (Wiley, 2019)
Explains construction professional practice in an appealing, succinct, and relatively informal way This book details the management of construction projects from beginning to end, concentrating on the principles underlying what construction professionals like architects do. It covers the entire process—from the initial meetings with clients through the design, recruitment of a contractor, contract management, construction, and handover—all without referencing legal cases, contract clause numbers, laws, statutes, or the complex jargon that can muddle comprehension. The first part of Professional Practice for Architects and Project Managers offers enlightening chapters that cover: professional standards, perks of the job, bonds and parent company guarantees, office meetings, letter writing, the RIBA Plan of Work, and Building Information Modelling (BIM). The second section teaches all about dealing with the clients, and includes chapters that discuss the extent of services, fee negotiations, conflicts of interest, and more. Next the book looks at such on-the-job responsibilities as surveys, ground investigations, cost estimates, work schedules, letters of intent, etc. The final section goes over everything readers need to know about dealing with a building contract in progress, informing them about advance payments, insurance, site inspections, contractor disputes, terminations, final certificates, and more. * Details the entire process of managing a construction project, including dealing with clients, the design process, running a construction project, and more * Highlights what the construction professionals do in their positions * Shows how principles of construction management are applied in practice * Written in a reader-friendly and accessible way Professional Practice for Architects and Project Managers is an excellent resource for architects and other construction professionals such as contract administrators, project managers, quantity surveyors, and contractors.